The magnitude and breadth of hepatitis C virus-specific CD8+ T cells depend on absolute CD4+ T-cell count in individuals coinfected with HIV-1. - Kim, A; Lauer, G; Ouchi, K; Addo, M; Lucas, M; Schulze Zur Wiesch, J; Timm, J; Boczanowski, M; Duncan, J; Wurcel, A; Casson, D; Chung, RT; et al. (2005)
CD8(+) T-cell responses are an essential antiviral host defense in persistent viral infections, and their sustained effectiveness is thought to be critically dependent on CD4(+) T-helper cells. To determine the relationship between HIV-1-induced CD4(+) T-cell depletion and hepatitis C virus (HCV)-specific CD8(+) T-cell responses during viral persistence, we studied 103 persons positive for HCV, 74 coinfected with HIV-1. CD8(+) T-cell responses to the entire HCV polyprotein were determined by using an interferon-gamma enzyme-linked immunospot (ELISpot) assay. Although HIV-1 infection by itself was not associated with a diminished HCV-specific response, HIV-1-associated CD4(+) depletion was associated with significantly lower HCV-specific CD8(+) T cells (R = 0.48, P < .0001). In contrast, declining CD4(+) counts over the same range were not associated with diminished Epstein-Barr virus (EBV)- (R = 0.19, P = .31) or HIV-1-specific (R = -0.13, P = .60) CD8(+) T-cell responses in persons infected with all viruses. These data indicate that frequencies of circulating HCV-specific CD8(+) T-cell responses are sensitive to absolute CD4(+) T-cell counts and provide a possible explanation for the accelerated HCV disease course in persons coinfected with HIV-1 and HCV.